Genetic polymorphism of NFKB1 and NFKBIA genes and liver cancer risk: a nested case–control study in Shanghai, China. Issue 2 (27th February 2014) - Gao, Jing; Xu, Hong-Li; Gao, Shan; Zhang, Wei; Tan, Yu-Ting; Rothman, Nat; Purdue, Mark; Gao, Yu-Tang; Zheng, Wei; Shu, Xiao-Ou; Xiang, Yong-Bing
Abstract : Objectives: Genetic variations of nuclear factor-κB (NF-κB) signalling pathway were found to be associated with inflammatory diseases and several malignancies. However, little is known about NF-κB pathway gene polymorphisms and susceptibility of liver cancer. The aim of this study was to investigate whether genetic variants of NFKB1 and NFKBIA were associated with risk of liver cancer in a Chinese population. Design: The study was designed as a nested case–control study within two prospective cohorts (the Shanghai Women's Health Study, SWHS, 1996–2000 and the Shanghai Men's Health Study, SMHS, 2002–2006). Settings: This population-based study was conducted in urban Shanghai, China. Participants: A total of 217 incident liver cancer cases diagnosed through 31 December 2009 and 427 healthy controls matched by sex, age at baseline (±2 years) and date (±30 days) of sample collection were included in the study. Primary and secondary outcome measures: Genetic polymorphisms of NFKB1 and NFKBIA were determined blindly by TaqMan single-nucleotide polymorphism (SNP) genotyping assay. OR and its 95% CIs were estimated by an unconditional logistic regression model to measure the association between selected SNPs and the risk of liver cancer. Results: After adjusted for potential confounding factors, rs28362491 ins/del or del/del genotypes were associated with higher risk of liver cancer with an adjusted OR 1.54 (95% CI 1.04 to 2.28). rs230496 AG and GG genotypes were also noted with higher risk of liver cancer with an adjusted OR 1.53 (95% CI 1.03 to 2.26). Haplotype analysis indicated that carriers of the NFKB1 GA and AA (rs230525-rs230530) haplotypes had higher risk of liver cancer under an additive model. No association was observed between NFKBIA variants and risk of live cancer. Conclusions: Our results suggest that genetic variants of NFKB1 influence liver cancer susceptibility in Chinese population, although replication in other studies is needed.